Preparation and characterization of cadmium (ll), zinc (ll) and copper (ll) ion complexes using new triazene ligands and study of their biological activity - Haneen Sadi Hussein; Mohammad Hamid Said; Ahmed Hassan Shantaf (Caspian Journal of Environmental Sciences)
The synthesis of novel ligand was disclosed in this study. This ligand was synthesized from reaction between 4-amino anti pyrene and 6-amino penicillanic acid by triazene reaction. The ligand was identified by FT-IR, UV-Visible, HNMR, Mass spectroscopy reacting the ligand with salts of transition metals Cu, Zn, Cd (II) complexes and gave octahedral, hybridization sp3d2 complexes with a molar ratio (1:2) M:L Magnetic Para-Di complexes were produced using amoral ratio of metal chloride to ligand spectroscopic data used to establish the identity of ligand of their corresponding complexes by FT-IR, UV-VIS, atomic absorption, magnetic susceptibility and conductivity. The ligand and its complex exhibited biological activity. It gave good results in inhibiting gram positive Streptococcus bacteria.